The Implementation of Distance Learning during the Covid-19 Pandemic - Utomo, Raden Adji Suryo; Mahmudah, Fitri Nur (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
The implementation of learning is the most important part in improving the quality of education. The Covid-19 pandemic period is part of the challenge for education so that learning continues. The purpose of this study was to investigate in depth the implementation of distance learning during the Covid-19 pandemic. The method used in this research is qualitative with a case study approach. The research was conducted at Muhammadiyah Pakel Elementary School. The data sources in this study were teachers, parents, and students. Data collection techniques using structured interviews assisted with guidelines that are structured questions systematically. Data analysis using the Denzin Licoln case study model assisted by atlas.ti software version 8. The technique used to improve the quality of research is source triangulation. The results of this study provide information that in the implementation of the implementation of distance learning there are three factors, namely policy, distance learning process, and human resource activeness. These three factors are novelty which can be recommendations for the three education centers in order to be part of improving the quality of distance learning education during the Covid-19 pandemic.